The benefits of coastal adaptation through conservation of foreshore vegetation. Issue 3 (15th February 2022) - Tiggeloven, Timothy; de Moel, Hans; van Zelst, Vincent T. M.; van Wesenbeeck, Bregje K.; Winsemius, Hessel C.; Eilander, Dirk; Ward, Philip J.
Abstract: Due to rising sea levels and projected socio‐economic change, global coastal flood risk is expected to increase in the future. To reduce this increase in risk, one option is to reduce the probability or magnitude of the hazard through the implementation of structural, Nature‐based or hybrid adaptation measures. Nature‐based Solutions in coastal areas have the potential to reduce impacts of climate change and can provide a more sustainable and cost‐effective alternative to structural measures. In this paper, we present the first global scale assessment of the benefits of conserving foreshore vegetation as a means of adaptation to future projections of change in coastal flood risk. In doing so, we extend the current knowledge on the economic feasibility of implementing global scale Nature‐based Solutions. We show that globally foreshore vegetation can contribute to a large decrease in both absolute and relative flood risk (13% of present‐day and 8.5% of future conditions in 2080 of global flood risk). Although this study gives a first proxy of the flood risk reduction benefits of conserving foreshore vegetation at the global scale, it shows promising results for including Nature‐based and hybrid adaptation measures in coastal adaptation schemes.